2017
DOI: 10.1038/s41526-017-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of space radiation and microgravity in DNA damage and DNA damage response

Abstract: In space, multiple unique environmental factors, particularly microgravity and space radiation, pose constant threat to the DNA integrity of living organisms. Specifically, space radiation can cause damage to DNA directly, through the interaction of charged particles with the DNA molecules themselves, or indirectly through the production of free radicals. Although organisms have evolved strategies on Earth to confront such damage, space environmental conditions, especially microgravity, can impact DNA repair r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 60 publications
2
98
0
2
Order By: Relevance
“…These results confirmed that space flight damaged nuclear DNA along tracks reflecting the tracks of space-radiation exposure [28]. Other recent studies have reported cH2AX signals in cells flown in space [29], as well as other forms of DNA damage, including chromosome aberrations in astronauts' lymphocytes [30]. High-LET radiation can thus induce permanent genetic changes in somatic and germ cells and is usually more effective per unit of absorbed dose than low-LET radiation.…”
Section: Detection Of Dna Damage Induced By Space Radiationsupporting
confidence: 82%
See 1 more Smart Citation
“…These results confirmed that space flight damaged nuclear DNA along tracks reflecting the tracks of space-radiation exposure [28]. Other recent studies have reported cH2AX signals in cells flown in space [29], as well as other forms of DNA damage, including chromosome aberrations in astronauts' lymphocytes [30]. High-LET radiation can thus induce permanent genetic changes in somatic and germ cells and is usually more effective per unit of absorbed dose than low-LET radiation.…”
Section: Detection Of Dna Damage Induced By Space Radiationsupporting
confidence: 82%
“…Several factors contribute to the large uncertainties in risk projection and hinder evaluations of the effectiveness of possible countermeasures, including radiation-quality effects at a low dose rate (ie, the inverse dose-rate effect, adaptive response, bystander effect, and cell competition) and microgravity [64]. To allow the assessment and management of human health risks in space, it is necessary to obtain more basic data on the combined effects of radiation under microgravity [30,65]. To address these serious problems, we developed 3-dimensional clinostat-synchronized heavy-ion and x-ray irradiation systems [66,67], which are expected to provide significant contributions to space radiation research, as a valuable platform for studies on the relative biological effectiveness and the combined effects of radiation under microgravity.…”
Section: Human Effect Of Space Radiationmentioning
confidence: 99%
“…From these terms, we observed several key pathways, including mitotic and cell cycle pathways, cancer-related pathways, hypoxia-related pathways, interferon pathways, and pathways related to radiation impact on cells ( Figure 6A). Cell cycle pathways [57], hypoxia [58], interferon dysregulation [59], and cancer [60][61][62] have all been observed in previous research studies as dysregulated due to spaceflight.…”
Section: Gsea C2: Curated Dataset Resultsmentioning
confidence: 65%
“…However, synergistic effects between radiation and μG have been reported [172][173][174][175][176][177], and they can sup-press each other's effects [172,178]. There is the still no consensus on whether radiation and μG have combined effects [179,180]. JAXA developed not only the Cell Biology Equipment Facility (CBEF) [181] but also a mouse habitat unit cage (MHU) [182], which provides long-term artificial gravity for control experiments in space.…”
Section: Biomed Research Internationalmentioning
confidence: 99%